Triangular radial Nb2O5 nanorod growth on c-plane sapphire for ultraviolet-radiation detection - Kim, Kwan Woo; Kim, Bum Jun; Lee, Sang Hoon; Nasir, Tuqeer; Lim, Hyung Kyu; Choi, Ik Jun; Jeong, Byung Joo; Lee, Jaeyeong; Yu, Hak Ki; Choi, Jae Young (RSC Advances, 2018)
Nb2O5 nanostructures with excellent crystallinities were grown on c-plane sapphire and employed for ultraviolet-(UV)-radiation detection. The triangular radial Nb2O5 grown on the c-sapphire substrate had a 6-fold symmetry with domain matching epitaxy on the substrate. Owing to the radial growth, the nanorods naturally connected when the deposition time increased. This structure can be used as a UV-detector directly by depositing macroscale electrodes without separation of a single nanorod and e-beam lithography process. It was confirmed that electric reactions occur at different UV irradiation wavelengths (254 nm and 365 nm).
Keywords: C-plane sapphire; Crystallinities; Deposition time; Domain matching epitaxy; e-Beam lithography; Nanorod growth; Radiation detection; UV irradiation